The Development of Intellectual Property Law: A Comparison of Northern and Southern Countries - Arabiyah, Syarifah (Faculty of Law, Universitas Pekalongan, 2024)
The development of intellectual property rights (IPR) law in the world has experienced significant dynamics along with technological advances and globalization. A comparison between Northern countries (developed countries) and Southern countries (developing countries) shows profound differences in the way IPR law is protected and implemented. Northern countries have more mature legal systems, strong infrastructure, and the ability to encourage innovation and effectively protect intellectual property rights. Digital technology, patents, copyrights, and trademarks in these countries are strictly protected, which drives the growth of a knowledge-based economy. On the other hand, Southern countries face major challenges related to IPR law enforcement, limited access to technology, and limited resources to protect and optimally utilize IPR. Although technology provides opportunities for developing countries to access global knowledge, gaps in protection and enforcement systems hinder their potential to innovate and compete in the international market. This article aims to analyze these differences and explore the challenges and opportunities that exist for Southern countries in facing increasingly complex and global IPR law developments